Wear behaviour of surface alloyed duplex stainless steel containing SiC ceramic particles - Paijan, Lailatul Harina; Maleque, Md. Abdul (2017)
This article presents an experimental investigation on the wear behaviour of surface alloyed duplex stainless steel (DSS) containing SiC ceramic particles using TIG melting technique. The SiC powder with 20 µm particle sizes was preplaced at 0.5 mg/mm2 and melting was conducted with energy inputs of 768 and 1280 J/mm. The room temperature wear behaviour of surface alloyed SiC duplex stainless steel was carried out against alumina ceramic ball using ball-on-disc tribometer. The effect of the process parameters on the wear resistance property was evaluated in this study. The surface alloyed DSS produced hardness value of about 3~4 times higher than substrate DSS material. It was revealed that surface alloying with SiC improved wear behaviour significantly with lower wear rate and coefficient of friction than the substrate material. This is due to the formation of SiC dendrites during re-solidification process that strongly bonded to the steel which in turn reduced the friction between surface alloyed surface and the counterpart alumina ball. The wear worn surface was observed under SEM with a very mild abrasive wear for surface alloyed DSS as compared to severe abrasive wear for DSS substrate surface. Moreover, surface alloyed DSS showed lower surface roughness and wear depth penetration indicating better wear behaviour of the sample. It can be concluded that the TIG torch melted surface alloyed DSS containing SiC can significantly improve the wear resistance of the material.